Frontal VP & VA Shunts Versus post parietal VP &VA Shunts - Khalili, A- Hadi; AL-Shalchy, Ali K. (Journal of the Faculty of Medicine Baghdad, 2005)
Background: Hydrocephalus is an imbalance of cerebro-spinal fluid (CSF) formation & absorption of sufficient magnitude to produce a net accumulation of fluid within to cerebral ventricles.Aim of study: the main objective of this study is to compare frontal with post parietal shunt regarding the surgery complications , end results & then to compare it with other studies abroad.Patient & Methods: this study included 920 patients admitted to the Neurosurgical department in the Hospital of surgical specialty,Medical city. The patients had full radiological study including MRI and CT . All patients were surgically managed & followed up for at least one year.Results: results were & compared regarding the type of surgery we did (VP&VA)shunt. frontal or parieted with other studies.Conclusion: frontal shunts can be as successful as post parieted shunts, & it carries less complications & lower mortalty although more difficult procedure & needs more experience